Demographic Dynamics and Economic Transformation in Nepal: Exploring the Interplay of Population Growth, Migration, and Development Pathways - Malla, Raju; Baral , Prabha; Shrestha , Rajendra Man (Nepal Population Journal, 2026)
This paper analyses the relationship between population change and economic development in Nepal from 1961 to 2021. It verifies that demographic transitions, such as population growth, fertility, and mortality evolution, are an intrinsic characteristic of global development and significantly influence the long-term social and economic trajectory of a nation. The main goals of this research are to analyse Nepal's trends in demographic change, to comment on its trends in economic growth, and to assess the effects of the major demographic indicators— like the working-age population, participation in the Labour force, and dependency ratio—on its economic growth. The research tries to bridge the gap in literature by including analysis for countries with recent data. The analysis utilizes a quantitative approach grounded in secondary data from various international and national sources. A multiple regression model, with Gross Domestic Product (GDP) as the dependent variable, was utilized in an analysis of key demographic independent variables like population growth rate, Labour force participation rate, and net migration. The regression results show that the model in total is extremely explanatory with an R² of 0.997 and is significant. This leads to the rejection of the null hypothesis, suggesting an extremely high correlation between economic growth and demographic variables. The indicators reveal positive contributions of the increase in Labour force and population to GDP, while youth population and net migration have negative effects, suggesting high youth dependency and high out-migration may deter economic development. It is concluded that while Nepal's demographic transition offers scope for speeding up economy, the same is threatened in the absence of policy action on education, employment, and social protection.